2010
DOI: 10.1371/journal.pone.0009006
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Kinetic Investigation of Streptococcus pyogenes Family GH38 α-Mannosidase

Abstract: BackgroundThe enzymatic hydrolysis of α−mannosides is catalyzed by glycoside hydrolases (GH), termed α−mannosidases. These enzymes are found in different GH sequence–based families. Considerable research has probed the role of higher eukaryotic “GH38” α−mannosides that play a key role in the modification and diversification of hybrid N-glycans; processes with strong cellular links to cancer and autoimmune disease. The most extensively studied of these enzymes is the Drosophila GH38 α−mannosidase II, which has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
46
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 65 publications
6
46
0
Order By: Relevance
“…Mannosidases in families GH38, GH47, and GH92, which are structurally and mechanistically distinct and hydrolyze a variety of ␣-mannosidic linkages, all require the coordination of a divalent metal ion in the catalytic site for activity. The divalent metal ion in the active site is thought to aid in distorting the substrate and stabilize the transition state by bridging the O2 and O3 hydroxyl groups of the mannoside bound in the Ϫ1 subsite (3,4,35). The absence of a participating metal ion in the GH125 mechanism reveals that divalent cation involvement is not a general requirement for efficient hydrolysis of ␣-mannosides.…”
Section: The Gh125 Enzymes Use An Inverting Catalytic Mechanism-mentioning
confidence: 99%
See 1 more Smart Citation
“…Mannosidases in families GH38, GH47, and GH92, which are structurally and mechanistically distinct and hydrolyze a variety of ␣-mannosidic linkages, all require the coordination of a divalent metal ion in the catalytic site for activity. The divalent metal ion in the active site is thought to aid in distorting the substrate and stabilize the transition state by bridging the O2 and O3 hydroxyl groups of the mannoside bound in the Ϫ1 subsite (3,4,35). The absence of a participating metal ion in the GH125 mechanism reveals that divalent cation involvement is not a general requirement for efficient hydrolysis of ␣-mannosides.…”
Section: The Gh125 Enzymes Use An Inverting Catalytic Mechanism-mentioning
confidence: 99%
“…␣-Mannosidases known to process N-glycans are found in families 38, 47, 76, 92, and 99. Very recent studies have shown the bacterial family 38 ␣-mannosidase from Streptococcus pyogenes (SpyGH38) to be a specific exo-␣1,3-mannosidase that is tolerant of the ␣1,6-branches in N-glycans (3). Analysis of family 92 glycoside hydrolases from the human gut symbiont Bacteroides thetaiotaomicron revealed an expanded repertoire of ␣-mannosidases (4).…”
mentioning
confidence: 99%
“…More recently, enzymes from Streptococcus pyogenes and Streptococcus pneumoniae classified in the GH38 (␣-1,3-mannosidase) and GH125 (␣-1,6-mannosidase) families, respectively, have been identified. These enzymes are active on N-glycans, highlighting the processing of N-glycans by Streptococcus bacteria (18,19). Finally, it was shown that the human pathogen Capnocytophaga canimorsus deglycosylates surface glycoproteins from the host and supports its growth on the released glycan moiety (20).…”
mentioning
confidence: 99%
“…1 In the absence of substrate in the active site, the coordination sphere of the bound metal ion is T 5 -square-based pyramidal with the four mentioned side chains and a single water molecule as ligands. 9,15 Of the two aspartyls complexing the metal ion, one is also the nucleophile in the otherwise classical catalytic machinery of the glycosidase retaining mechanism. 1 The divalent metal ion bound to the active site is a prerequisite for binding of the substrate.…”
mentioning
confidence: 99%